Enhancing Diabetic Retinopathy Detection Using Optimized Deep Learning Techniques with ResNet - Gangopadhyay, Tansu; Patra, Saptaparno; S, Deepajothi (International Journal of Computer Sciences and Engineering, 2025)
Diabetic retinopathy (DR) is an extreme complication of diabetes and a main reason of vision impairment worldwide. Early detection is essential for powerful treatment and prevention of blindness. In this paper, we gift a deep learning approach for the automatic detection of DR the use of ResNet, a convolutional neural network (CNN) architecture known for its intensity and excessive performance in photo reputation obligations. Our examine utilizes a big dataset of retinal fundus pictures, which undergo preprocessing and augmentation to beautify the version’s robustness. The ResNet model is exceptional-tuned to classify specific stages of DR with an excessive diploma of accuracy. The consequences exhibit that our version achieves a class accuracy of 94.3%, appreciably enhancing detection competencies as compared to standard techniques. This paper explores using switch getting to know and optimization techniques to cope with demanding situations along with overfitting and dataset imbalance, in the end offering a green, scalable solution for computerized diabetic retinopathy screening.